1992
DOI: 10.1073/pnas.89.15.6803
|View full text |Cite
|
Sign up to set email alerts
|

Entropic stabilization of a mutant human lysozyme induced by calcium binding.

Abstract: The stabilization mechanism of the mutant human lysozyme with a calcium binding site (D86/92) was investigated by using calorimetric approaches. By differential scanning calorimetry, the enthalpy change (Al) in the unfolding of holo-D86/92 was found to be 6.8 kcal/mol smaller than that of the wild-type and apo-D86/92 lysozymes at 85TC.However, the unfolding Gibbs energy change (AG) of the holo mutant was 3.3 kcal/mol greater than the apo type at 85C, indicating a significant decrease of entropy (TAS = 10.1 kca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
37
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 23 publications
(17 reference statements)
8
37
0
Order By: Relevance
“…Analysis of the dependence of the reciprocal of the rate constant on [Caz' 1, according to the model developed by Sancho et al (1 991), indicates that native trypsinogen in 4 M GdmCl can bind Caz+ only twofold weaker than in the absence of denaturant. Such binding effects are perhaps not unusual, as unfolded mutated human lysozyme exhibits rather strong affinity for CaL+ (Kuroki et al, 1992). Further, our analysis indicates that liganded trypsinogen unfolds sixfold slower than the Ca-free form (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Analysis of the dependence of the reciprocal of the rate constant on [Caz' 1, according to the model developed by Sancho et al (1 991), indicates that native trypsinogen in 4 M GdmCl can bind Caz+ only twofold weaker than in the absence of denaturant. Such binding effects are perhaps not unusual, as unfolded mutated human lysozyme exhibits rather strong affinity for CaL+ (Kuroki et al, 1992). Further, our analysis indicates that liganded trypsinogen unfolds sixfold slower than the Ca-free form (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…These have included the incorporation of metal binding sites [45], elimination of a buried solvent molecule [46] and addition of a peptide β-hairpin [47]. Detailed comparison of mesophilic and extremely thermophilic enzymes has led to suggestions that the elimination of cavities within the enzyme structure and a decrease in the number of surface loops [48] may be ways of achieving greater stability.…”
Section: Conformational Stability At High Temperatures : Theoretical mentioning
confidence: 99%
“…We have already found that only the double mutation (Gln-86 3 Asp and Ala-92 3 Asp) in human lysozyme resulted in the formation of a Ca 2ϩ binding site (5). The precise analyses of the stability (3,5,6) and the Ca 2ϩ affinity (7) using calorimetry have also been performed, and the high resolution structural data of the wild type (12) and Ca 2ϩ binding mutant (13) lysozymes from x-ray crystallography are available. Here we show the effect of the subsequent mutations (Gln-86 3 Asp, Ala-92 3 Asp, and Ala-83 3 Lys) on the Ca 2ϩ binding properties, conformational stabilities, and tertiary structures of these mutants.…”
mentioning
confidence: 99%
“…How does the introduction of charged residues within a calcium binding site affect the stability and Ca 2ϩ binding behavior? There are some reports describing the effect of mutations within Ca 2ϩ binding sites on the stability of the protein (3,4). Our approach in this paper is to introduce the minimum perturbation by amino acid replacement and determine the effect of these mutations on the stability and the Ca 2ϩ binding function using calorimetry.…”
mentioning
confidence: 99%
See 1 more Smart Citation